Modeling Topographic Variables in Relation to Land Cover and Land Use Changes in Hail City - Al-Shammari, Afaf Salem; Al-Nisayan, AbdulRahman Suleiman (Journal of natural sciences, life and applied sciences, 2025)
The study aims to elucidate the factors affecting land cover, land use, and their changes, as well as their environmental and developmental impacts in the city of Hail. It begins by analyzing the distribution of active forces in land cover and land use changes in the city and modeling the spatial relationships between them. The study monitored land cover and land use changes and revealed the environmental and developmental effects of these changes during this period. This was accomplished using remote sensing data and geographic information systems to track these changes that have affected—and will continue to affect—land cover and land use in Hail City, with the goal of providing information about the rate of land use pattern changes. Among the key findings, the modeling results showed strong correlations (with 99% confidence) between urban expansion and various factors including geological structures, soil composition, wadi channels, population size, services, and distance from peripheries. These correlations were either positive or negative. However, regarding the relationship between urban expansion and factors such as topographic elevation, temperature distribution, and humidity, the results indicated weak positive correlations. The study recommended maintaining the pattern of land cover and land use changes in Hail City in a way that supports sustainable development plans for the city, in alignment with the objectives of Vision 2030.